2005
DOI: 10.1074/jbc.m410943200
|View full text |Cite
|
Sign up to set email alerts
|

Nectin-4, a New Serological Breast Cancer Marker, Is a Substrate for Tumor Necrosis Factor-α-converting Enzyme (TACE)/ADAM-17

Abstract: Serum markers are extensively used in diagnostic and follow-up of cancer patients. We recently described Nectin-4, a 66-kDa adhesion molecule of the Nectin family, which is a valuable new histological and serological marker for breast carcinoma. In vivo, Nectin-4 is re-expressed in breast carcinoma, and a circulating form of Nectin-4 is detected in the sera of patients with metastatic breast cancer. In vitro, a soluble form of Nectin-4 is produced in the supernatant of breast tumor cell lines (S. Fabre-Lafay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
99
1
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(105 citation statements)
references
References 43 publications
(19 reference statements)
2
99
1
2
Order By: Relevance
“…Ectodomain shedding essentially disrupts cell adhesion and supports cell movement (Arribas and Borroto, 2002). In terms of cell adhesion, E-and N-cadherin, ␥-protocadherin, nectin-1 and -4, and desmoglein-2 have all been shown to be cleaved specifically in their ectodomains by ADAM proteins (Kim et al, 2002;Fabre-Lafay et al, 2005;Haas et al, 2005;Maretzky et al, 2005;Reiss et al, 2005Reiss et al, , 2006BechSerra et al, 2006). Surprisingly, integrins only serve as ligands for ADAMs (Seals and Courtneidge, 2003;White, 2003); they have not been reported to be cleaved by members of the ADAM protein family.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…Ectodomain shedding essentially disrupts cell adhesion and supports cell movement (Arribas and Borroto, 2002). In terms of cell adhesion, E-and N-cadherin, ␥-protocadherin, nectin-1 and -4, and desmoglein-2 have all been shown to be cleaved specifically in their ectodomains by ADAM proteins (Kim et al, 2002;Fabre-Lafay et al, 2005;Haas et al, 2005;Maretzky et al, 2005;Reiss et al, 2005Reiss et al, , 2006BechSerra et al, 2006). Surprisingly, integrins only serve as ligands for ADAMs (Seals and Courtneidge, 2003;White, 2003); they have not been reported to be cleaved by members of the ADAM protein family.…”
Section: Cytokines and Growth Factorsmentioning
confidence: 99%
“…In addition, several studies have shown that TACE expression is elevated under pathological conditions. In mammary tumor tissues, TACE protein levels are higher than in normal tissues (13,14). Also, elevated levels of TACE mRNA expression were found in osteoarthritis (15) and rheumatoid arthritis (RA)-affected cartilage as compared with normal cartilage (16), suggesting that abnormal TACE activity may contribute to the development of several pathological conditions, including RA.…”
mentioning
confidence: 99%
“…TIGIT/WUCAM Introduction CD155 represents an Ig-like glycoprotein [1] and is the founder of a subfamily of adhesion receptors comprising also the related nectins 1-4. CD155/nectins take part in the complex regulation of cell growth, differentiation and motility [2,3], thereby in part explaining their identification as tumor markers [4][5][6][7]. Current evidence suggests that in contrast to nectins, CD155 acquired immunologically relevant functions.…”
mentioning
confidence: 99%